The lingual articulation of devoiced /u/ in Tokyo Japanese. (January 2018) - Shaw, Jason A.; Kawahara, Shigeto
Highlights: First lingual articulatory study of devoiced /u/ in Tokyo Japanese. Devoicing of /u/ shortens temporal interval between flanking consonants. There is variation across words and speakers in whether /u/ is specified for a vowel height target. Tokens that lack a vowel height target also show indications of temporal reorganization. Abstract: In Tokyo Japanese, /u/ is typically devoiced between two voiceless consonants. Whether the lingual vowel gesture is influenced by devoicing or present at all in devoiced vowels remains an open debate, largely because relevant articulatory data has not been available. We report ElectroMagnetic Articulography (EMA) data that addresses this question. We analyzed both the trajectory of the tongue dorsum across VC1 uC2 V sequences as well as the timing of C1 and C2 . These analyses provide converging evidence that /u/ in devoicing contexts is optionally targetless—the lingual gesture is either categorically present or absent but seldom reduced. When present, the magnitude of the lingual gesture in devoiced /u/ is comparable to voiced vowel counterparts. Although all speakers produced words with and without a vowel height target for /u/, the frequency of targetlessness varied across speakers and items. The timing between C1 and C2, the consonants flanking /u/ was also effected by devoicing but to varying degrees across items. The items with the greatest effect of devoicing on this inter-consonantal interval were also the items with the highest frequency of vowel height targetlessness for devoiced /u/.